Advancement in Plant Tissue Culture-Based Research for Sustainable Exploitation of Well-Known Medicinal Herb Bacopa Monnieri - Vinod, Abhijith; Sharma, Shivika; Sharma, Vikas (Universitas Gadjah Mada, 2023)
The current review focuses on the plant Bacopa monnieri, one of prominent medical herbs in Indian ayurvedic system. The plant is well known for its cognitive and memory enhancing capabilities. The plant contains many useful alkaloids and secondary metabolites. Studies have shown that it has various promising pharmacological properties which have the potential to treat many illnesses and disorders such as asthma, bronchitis, rheumatism also in for renal disease, water retention, blood cleaning etc. This leads to the over exploitation of the plant which puts a stress on the naturally available stock of the plant, therefore, it becomes a necessity to find optimum methods for mass production of the plant and its important secondary metabolites. This review attempts to compile and to discuss the advancements in methods and techniques including type of culture vessels, plant growth regulators (PGRs), effect of stress, plant growth promoting rhizobacteria (PGPRs) interactions; for in vitro propagation of Bacopa monnieri and the enhanced production of its important bioactive (bacoside) for its sustainable exploitation.